No Direct Role for Epstein-Barr Virus in American Hepatocellular Carcinoma - Chu, Peiguo G. (American Society for Investigative Pathology, 2001)
Epstein-Barr virus (EBV) was recently linked to hepatocellular carcinogenesis in Japanese patients. It is not clear whether EBV infection is also associated with hepatocellular carcinoma (HCC) occurring in American patients. We studied 41 cases of HCC from the Los Angeles area for evidence of EBV infection by in situ hybridization, immunohistochemistry, and polymerase chain reaction methods. Of 41 cases, 16 were seropositive for hepatitis B virus surface antigen (39%), 9 of 29 tested were seropositive for hepatitis C virus antibody (31%); in total, 22 cases were seropositive for hepatitis B virus and/or hepatitis C virus (53%). Of 41 cases, 1 was positive for EBV-encoded small nonpolyadenylated RNA (EBER)-1 (2%) by in situ hybridization. By immunohistochemistry, two cases were positive for EBV nuclear antigen (EBNA)-1 (5%), one was positive for the transactivating immediate early BZLF1 (ZEBRA) (2%), and none was positive for latent membrane protein-1. None of the 41 cases was positive for latent membrane protein-1 and EBV nuclear antigen (EBNA)-4 DNAs by polymerase chain reaction assay. All four positive cases showed rare EBER-1-, ZEBRA-, or EBNA-1- positive cells (<0.1%); in none of these cases was there expression of any other EBV viral genes. In the one case each that was positive for EBER-1 and ZEBRA, both of which occurred in patients of non-Asian ethnicity, the staining was limited to infiltrating small lymphocytes, and tumor cells were negative. In the two cases that were positive for EBNA-1, both of which occurred in patients of Asian ethnicity, the staining was limited to tumor cells, and infiltrating small lymphocytes were negative. Our study indicates that rare cases of American HCC may contain EBV-infected cells, but it is unlikely that EBV plays a major role in the carcinogenesis of HCC.